PENINGKATAN KEMAMPUAN MENGHAFAL ASMAUL HUSNA MELALUI MEDIA FLASHCARD DI RA CAHAYA QUR’AN BANJARSARI SAYUNG DEMAK - Chumaidah; Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2025)
The background of this research problem is that students at RA Cahaya Qur'an Banjarsari Sayung Demak are less stimulated in their potential, caused by the media used in memorizing, namely blackboards and chalk which are less effective for children in memorizing Asmaul Husna. In addition, the use of monotonous media, so that children are less motivated. Flashcard media as one of the alternative media studied to determine the increase in the ability to memorize Asmaul Husna. This research method uses Qualitative Descriptive and data collection techniques through observation, interview and documentation techniques. The subjects used were group A students totaling 19 children. Data sources come from educators and education personnel. The results of this study indicate that the Application of Flashcard Media by showing cards and memorizing repeatedly, and is carried out through three stages, namely the preparation stage, the implementation stage with a 4-step approach (planning, action, observation and reflection), and the authentic assessment stage. In the ability to memorize Asmaul Husna 1-10 has increased and can be said to be successful according to the criteria for children's learning success, namely increasing well.